If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 10x + -16 = 74 Reorder the terms: -16 + 10x = 74 Solving -16 + 10x = 74 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 10x = 74 + 16 Combine like terms: -16 + 16 = 0 0 + 10x = 74 + 16 10x = 74 + 16 Combine like terms: 74 + 16 = 90 10x = 90 Divide each side by '10'. x = 9 Simplifying x = 9

| 1.32g-8=0.58 | | 6(5+7z)= | | 9x+8=71 | | 42=8m-13m | | 2(-x-1)=2x-34 | | 3(x-1)+5=25 | | 5(-7z-6)= | | 49x^2-196=0 | | 5t-0=-3t+7 | | 3(-14+2)=4(5-14) | | -5(n+8)=-98 | | 4g+3g+9g= | | x^2-13x=-30 | | 4(3x-2)=52 | | 5x^2-24x+18=0 | | 3x^2-6x+45=0 | | x^2-13=-30 | | 32+5(8.6)=n | | 5r+r+4r= | | 24=5x+6-2x | | 11r-6r+5r=168 | | 32+5(8.6)= | | 3(-14+2)=4(5-13) | | 3y+10=9 | | 3m-4=2m-13 | | 41+8z=-z^2 | | 8x+12=100 | | b-3+3b=36 | | 3y+7=9 | | 4(y+2)=5(y-5) | | 6x-10=-18x-4 | | 3x^2-15x+45=0 | | 2(-2+x)-1(x-4)=0 | | (x-6)(5x+3)=0 | | 27=y | | (x+3)(6x+7)=0 | | 2y-8=-y+4 | | 6x^2-8x+3=0 | | 0=-5h-2h | | 4h*6h= | | -2+2y=-4 | | 3-4r=10r+10 | | (3m-4n-7)-(8m+n-6)= | | 32+5n=75 | | 2y=4x-3 | | 2+11x=12x-6 | | (3m-4n-7)(8m+n-6)= | | y^2-16x-6y+25=0 | | 3(a-2)=9(a+2) | | 9x-15= | | 3=12-3x | | -7h-4=h+4 | | 62-c=42 | | -3b-2a-4c+5b-8a= | | 4d-8=19 | | 4(x-4)-11x= | | 6c-12=48 | | 25h=20h+15 | | 1-2x=16-5x | | 4y+6=-14 | | 9(6x+3)= | | 7x=11x+16 | | 3x+-7=-8 | | 9a-4a+a-10= | | 6w+5=w-35 |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions